A nano-hybrid MoS2 / Mo2CT x Composite materials and their synthesis methods and applications
By directly sulfidizing MoS2 on the Mo2CTx conductive matrix to form a MoS2/Mo2CTx composite material with accordion structure, the problem of molybdenum disulfide in sodium ion capacitors is solved, and the high capacity and cyclic stability of sodium ions are achieved Battery and capacitor negative material.
Patent Information
- Application Number
- CN202111505178.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-10
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-12-10
AI Technical Summary
As the negative electrode material of sodium ion capacitor, molybdenum disulfide causes structural damage and capacity attenuation due to volume expansion during charging and discharging, and the precursor process for preparing composite materials is cumbersome and difficult to produce in industrialized production.
MoS2 is directly sulfidized on the Mo2CTx conductive substrate to form a nanohybrid MoS2/Mo2CTx composite material with accordion structure, as the negative electrode material for sodium ion batteries or capacitors, and Mo2CTx is used as the Mo source and conductive substrate of MoS2 to simplify the preparation process.
It significantly improves the capacity and cycle stability of sodium ion batteries and capacitors, simplifies the preparation process, is suitable for large-scale production, and suppresses the irreversible attenuation of polysulfides.
Smart Images

Figure CN114203995B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery electrode materials, and in particular to a nano-hybrid MoS2 / Mo2CT x Composite materials and their synthesis methods and applications. Background Art
[0002] The information disclosed in this background section is intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Faced with increasingly prominent energy problems, people have an increasing demand for new energy-saving and environmentally friendly devices. Lithium-ion batteries and capacitors have begun to be widely used in daily life. Due to the limited lithium resources on the earth, sodium, which is abundant, cheap, and has similar chemical properties to lithium, is an advantageous candidate material for the next generation of energy storage devices. Sodium-ion capacitors have become an emerging energy storage device by combining the advantages of high power density of batteries and high energy density of capacitors with their hybrid storage mechanism. However, the development of sodium-ion capacitors is limited by problems such as the difficulty in matching the positive and negative electrode capacities, the poor negative electrode capacity, and the pulverization of negative electrode materials during the cycle. Therefore, it is imperative to develop negative electrode materials with high electronic conductivity, high capacity and stable structure.
[0004] Transition metal sulfides have aroused people's research enthusiasm once they were discovered due to their unique two-dimensional structure. In particular, molybdenum disulfide has high electrochemical activity, high specific capacity, and low price during charging and discharging, especially when sodium is inserted and removed, the cycle reversibility and first coulombic efficiency are relatively high. However, when molybdenum disulfide is used as the negative electrode material of sodium ion capacitors, due to the large ionic radius of sodium ions, the process of sodium ion insertion and removal will cause serious volume expansion, leading to material agglomeration, structural damage, and shedding from the current collector surface. In addition, molybdenum disulfide will produce a large amount of polysulfide polymers during deep charging and discharging, which is prone to produce a "shuttle effect", resulting in irreversible capacity decay.
[0005] In order to solve the problem of capacity attenuation of MoS2 as a negative electrode material during sodium ion storage, two methods are often used: compounding with conductive buffer materials or constructing nanostructures. For example, it has been reported that MoS2 can be used to store Mo3C2T3 by hydrothermal method. x In-situ generation of MoS2 nanosheets between layers to form MoS2 / Ti3C2T X The composite structure of MoS2 nanosheets uniformly modified on the MXene conductive network can be used as the negative electrode material of sodium ion batteries at 1A g -1 It can reach 162.7mAh g -1 The reversible specific capacity of Nb2CT xGrowth of carbon-coated MoS2 nanosheets (Nb2CT) on MXene framework x @MoS2@C). This special structure exhibits high specific capacity and good rate performance at 40 A g -1 At a current density of 260 mAh g -1 However, the preparation process of the precursors for preparing the final product in the above literature is too complicated and difficult to be industrialized. Summary of the invention
[0006] The present invention provides a nano hybrid MoS2 / Mo2CT x Composite material and synthesis method and application thereof, wherein MoS2 in the composite material is Mo2CT x Direct vulcanization synthesis, no need to add Mo2CT x External Mo source to form MoS2 / Mo2CT with accordion structure x A composite material, when used as a negative electrode material of a sodium ion battery or capacitor, can significantly improve the capacity and cycle stability. To achieve the above purpose, the present invention discloses the following technical solution.
[0007] In a first aspect of the present invention, a nano-hybrid MoS2 / Mo2CT is disclosed. x Composite material, the two-dimensional structure of MoS2 is in situ bonded to the Mo2CT x The conductive substrate surface and the conductive substrate, that is, the MoS2 and Mo2CT x Conductive matrix mixed distribution.
[0008] In a second aspect of the present invention, a nano-hybrid MoS2 / Mo2CT x The synthesis method of the composite material comprises the following steps:
[0009] (1) Mix the solution containing sulfur powder with Mo2CT x The aqueous solution is mixed, the pH of the reaction system is adjusted to acidic, the solid product in the reaction system is separated, washed and dried to obtain S / Mo2CT x .
[0010] (2) In an oxygen-isolating environment created by a flowing protective gas, sulfur powder is placed upstream of the protective gas, and the S / Mo2CT x Placed downstream of the protective gas, the sulfur powder is heated to form sulfur vapor, which converts the S / Mo2CT x The Mo2C in the solution is in situ reduced to Mo2S, thus obtaining MoS2 / Mo2CT. x Composite materials.
[0011] Furthermore, in step (1), the Mo2CT x It is better to control the mass ratio of sulfur powder between 1:3 and 8, such as 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, etc.
[0012] Furthermore, in step (1), the solution containing sulfur powder is formed by dissolving sulfur powder in ethylenediamine. Preferably, the mass concentration of sulfur powder in the solution is controlled to be 20-70 mg / mL. In this step, the main function of the ethylenediamine is to dissolve the sulfur powder and help to evenly disperse it in the liquid phase.
[0013] Furthermore, in step (1), the Mo2CT x The aqueous solution is made of Mo2CT x Preferably, the solution contains Mo2CT x The concentration was controlled at 0.4~0.8 mg / mL.
[0014] Furthermore, in step (1), the solution containing sulfur powder is mixed with Mo2CT x After the aqueous solution is mixed, the stirring time is not less than 1 hour, and then the pH of the reaction system is adjusted to acidic, so that the sulfur powder can be fully combined with Mo2CT x Optionally, hydrochloric acid, sulfuric acid, nitric acid, or acetic acid is used to adjust the pH of the reaction system to between 1 and 3. The acid is added to form an ionic compound with ethylenediamine so that it can be removed in subsequent water washing.
[0015] Furthermore, in step (1), the reaction system is stirred for not less than 12 hours after the pH of the reaction system is adjusted.
[0016] Furthermore, in step (1), the solid product is washed to neutrality to prevent the residual acid from causing adverse effects on subsequent reactions and instruments.
[0017] Furthermore, in step (1), the drying temperature is 50-80° C., and the drying time is 10-24 hours.
[0018] Furthermore, in step (2), the Mo2CT x It is better to control the mass ratio of sulfur powder between 1:10 and 50, such as 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, etc.
[0019] Furthermore, in step (2), the heating temperature is 400-800°C and the reaction time is 2-4 hours. During the gas phase sulfurization treatment, the sulfur powder generates reducing sulfur vapor at high temperature.x The Mo2C in the solution is in situ reduced to Mo2S, thus obtaining MoS2 / Mo2CT. x It should be noted that this step requires controlling the heating temperature and reaction time to avoid the S / Mo2CT x The Mo2C in the solution is completely converted into MoS2. In addition, in step (1), Mo2CT x Sulfur powder is mixed into the Mo2CT x MoS2 is formed in situ in the center and on the surface, that is, the MoS2 and Mo2CT x Conductive matrix mixed distribution.
[0020] Furthermore, in step (2), the protective gas includes any one of argon, nitrogen or helium, or a combination of at least two of them; typical but non-limiting combinations are a combination of argon and nitrogen, a combination of nitrogen and helium, and a combination of argon, nitrogen and helium.
[0021] Furthermore, in step (2), the flow rate of the protective gas is 40-100 SCCM.
[0022] Furthermore, in step (2), the heating rate is preferably controlled between 2 and 5°C / min, such as 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, etc.
[0023] In a third aspect of the present invention, the MoS2 / Mo2CT x The application of composite materials in energy storage devices, such as negative electrode materials for sodium ion batteries and sodium ion capacitors, can effectively inhibit the "shuttle effect" of polysulfides and improve the electrochemical performance of sodium ion batteries and sodium ion capacitors.
[0024] Compared with the prior art, the present invention has the following beneficial and unique effects:
[0025] (1) MoS2 / Mo2CT provided by the present invention x In composite materials, Mo2CT x MoS2 with a two-dimensional structure is in situ generated on the surface. In the preparation of this composite material, Mo2CT x It can be used as a Mo source for MoS2 and as a conductive matrix to improve the conductivity of MoS2. The two can work together to effectively improve the electrochemical performance of sodium ion batteries and sodium ion capacitors. This is because: MoS2 / Mo2CT x The composite material inherits Mo2CT xGood conductivity and good cycle stability can speed up the transmission of electrons and obtain a longer cycle life. x The MoS2 nanosheets that start growing on the surface and continue to grow in situ have high specific capacity and chemical activity, thereby obtaining higher specific capacity and initial efficiency. x Composite materials are a more ideal sodium storage negative electrode material.
[0026] (2) MoS2 / Mo2CT of the present invention x The MoS2 in the composite material is Mo2CT x Direct sulfurization synthesis to form MoS2 / Mo2CT with accordion structure x The structure has more active sites and provides higher capacity, and Mo2CT x The presence of can increase its cycle stability. When the composite material is used as the negative electrode material of sodium ion battery or capacitor, the capacity and cycle stability can be significantly improved.
[0027] (3) Compared with the existing preparation methods of composite materials of MoS2 loaded on graphene sheets or other non-Mo-based MXenes, the preparation method of the MoS2 / Mo2CTx composite material provided by the present invention requires fewer types of raw materials and simpler steps, so that the product has higher purity and is more suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein:
[0029] Figure 1 The precursor Mo2CT prepared in the first embodiment of the present invention is x SEM images of .
[0030] Figure 2 The precursor Mo2CT prepared in the first embodiment of the present invention is x XRD pattern of .
[0031] Figure 3 The MoS2 / Mo2CT prepared in the first embodiment of the present invention x SEM images of the composite materials.
[0032] Figure 4 The MoS2 / Mo2CT prepared in the first embodiment of the present invention x TEM (a) and HRTEM (b) of the composite material.
[0033] Figure 5 The MoS2 / Mo2CT prepared in the first embodiment of the present invention x XRD patterns of the composite materials.
[0034] Figure 6 The MoS2 / Mo2CT prepared in the first embodiment of the present invention x Composite materials as negative electrode materials for sodium ion batteries (current density 0.1A g -1 ) of the cycle data.
[0035] Figure 7 The MoS2 / Mo2CT prepared in the first embodiment of the present invention x Composite materials as negative electrode materials for sodium ion capacitors (current density 1 A g -1 ) of the cycle data.
[0036] Figure 8 This is the XRD spectrum of MoS2 prepared in the sixth embodiment of the present invention.
[0037] Fig. 9 The MoS2 prepared in the sixth embodiment of the present invention is used as the negative electrode material of the sodium ion battery (current density is 0.1Ag -1 ) of the cycle data. Specific embodiments
[0038] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0039] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the present invention are for demonstration purposes only. The present invention is further described according to the accompanying drawings and specific embodiments of the specification.
[0040] First embodiment
[0041] A MoS2 / Mo2CT x The method for preparing the composite material comprises the following steps:
[0042] (1) Take 15 mL of deionized water and place it in the inner lining of a 50 mL reactor. Then add 15 mL of concentrated hydrochloric acid (concentration is 12 mol / L) and 0.5 g of lithium fluoride to the inner lining and stir with a magnetic stirrer until the lithium fluoride is completely dissolved in the deionized water. Then add 0.5 g of MAX phase Mo2Ga2C and continue stirring for 1 hour to obtain a precursor solution for use.
[0043] (2) The liner containing the precursor solution was placed in a reactor, and then the temperature was raised to 160°C and kept at this temperature for 72 hours. After natural cooling, the obtained reaction solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid product was placed in a dryer and dried at 60°C for 12 hours to obtain a gray powder precursor (i.e., Mo2CT x ),spare.
[0044] (3) Take 0.1 g of the precursor prepared in step (2) and dissolve it in 200 mL of water and stir to form a uniformly dispersed MXene aqueous solution. Take 500 mg of sulfur powder and dissolve it in 10 mL of ethylenediamine. After it is completely dissolved, add it dropwise to the MXene aqueous solution. After stirring for 1.5 hours, add dilute hydrochloric acid (concentration of 3 mol / L) until the pH is 1. Continue stirring for 12 hours to obtain a precursor solution for use.
[0045] (4) The precursor solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid was placed in a dryer and dried at 60°C for 12 hours to obtain a yellow-brown powder precursor (i.e., S / Mo2CT x ),spare.
[0046] (5) Take 0.1g of the precursor and place it in a porcelain boat (recorded as porcelain boat 1), then take 3g of sulfur powder and place it in this photo (recorded as porcelain boat 2), place porcelain boat 2 in the upstream of the protective gas flow of the tubular furnace, and place porcelain boat 1 in the downstream of the protective gas flow of the tubular furnace. The protective gas is flowing nitrogen (flow rate is 70 SCCM). After completion, heat it to 600℃ at a rate of 2℃ / min and keep it warm for 4 hours. After the insulation is completed, cool it naturally to obtain the target product MoS2 / Mo2CT x .
[0047] Second embodiment
[0048] A MoS2 / Mo2CT x The method for preparing the composite material comprises the following steps:
[0049] (1) Take 15 mL of deionized water and place it in the inner lining of a 50 mL reactor. Then add 15 mL of concentrated hydrochloric acid (concentration is 12 mol / L) and 0.5 g of lithium fluoride to the inner lining and stir with a magnetic stirrer until the lithium fluoride is completely dissolved in the deionized water. Then add 0.5 g of MAX phase Mo2Ga2C and continue stirring for 1 hour to obtain a precursor solution for use.
[0050] (2) The liner containing the precursor solution was placed in a reactor, and then the temperature was raised to 180°C and kept at this temperature for 72 hours. After natural cooling, the obtained reaction solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid product was placed in a dryer and dried at 60°C for 12 hours to obtain a gray powder precursor (i.e., Mo2CT x ),spare.
[0051] (3) Take 0.1 g of the precursor prepared in step (2) and dissolve it in 250 mL of water and stir to form a uniformly dispersed MXene aqueous solution. Take 400 mg of sulfur powder and dissolve it in 20 mL of ethylenediamine. After it is completely dissolved, add it dropwise to the MXene aqueous solution. After stirring for 1.5 hours, add dilute hydrochloric acid (concentration of 3 mol / L) until the pH is 1. Continue stirring for 12 hours to obtain a precursor solution for use.
[0052] (4) The precursor solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid was placed in a dryer and dried at 55°C for 20 hours to obtain a yellow-brown powder precursor (i.e., S / Mo2CT x ),spare.
[0053] (5) Take 0.1g of the precursor and place it in a porcelain boat (recorded as porcelain boat 1), then take 5g of sulfur powder and place it in this photo (recorded as porcelain boat 2), place porcelain boat 2 in the upstream of the protective gas flow of the tubular furnace, and place porcelain boat 1 in the downstream of the protective gas flow in the tubular furnace. The protective gas is flowing nitrogen (flow rate is 50 SCCM). After completion, heat to 500℃ at a rate of 2℃ / min and keep warm for 3 hours. After the insulation is completed, cool naturally to obtain the target product MoS2 / Mo2CT x .
[0054] Third embodiment
[0055] A MoS2 / Mo2CT x The method for preparing the composite material comprises the following steps:
[0056] (1) Take 15 mL of deionized water and place it in the inner lining of a 50 mL reactor. Then add 15 mL of concentrated hydrochloric acid (concentration is 12 mol / L) and 0.5 g of lithium fluoride to the inner lining and stir with a magnetic stirrer until the lithium fluoride is completely dissolved in the deionized water. Then add 0.5 g of MAX phase Mo2Ga2C and continue stirring for 1 hour to obtain a precursor solution for use.
[0057] (2) The liner containing the precursor solution was placed in a reactor, and then the temperature was raised to 160°C and kept at this temperature for 80 hours. After natural cooling, the obtained reaction solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid product was placed in a dryer and dried at 60°C for 12 hours to obtain a gray powder precursor (i.e., Mo2CT x ),spare.
[0058] (3) Take 0.1 g of the precursor prepared in step (2) and dissolve it in 200 mL of water and stir to form a uniformly dispersed MXene aqueous solution. Take 800 mg of sulfur powder and dissolve it in 20 mL of ethylenediamine. After it is completely dissolved, add it dropwise to the MXene aqueous solution. After stirring for 1.5 hours, add dilute hydrochloric acid (concentration of 3 mol / L) until the pH is 1. Continue stirring for 12 hours to obtain a precursor solution for use.
[0059] (4) The precursor solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid was placed in a dryer and dried at 80°C for 10 hours to obtain a yellow-brown powder precursor (i.e., S / Mo2CT x ),spare.
[0060] (5) Take 0.1g of the precursor and place it in a porcelain boat (recorded as porcelain boat 1), then take 2.5g of sulfur powder and place it in this photo (recorded as porcelain boat 2), place porcelain boat 2 in the upstream of the protective gas flow of the tubular furnace, and place porcelain boat 1 in the downstream of the protective gas flow in the tubular furnace. The protective gas is flowing nitrogen (flow rate is 100 SCCM). After completion, heat to 400℃ at a rate of 2℃ / min and keep warm for 4 hours. After the insulation is completed, cool naturally to obtain the target product MoS2 / Mo2CT x .
[0061] Fourth embodiment
[0062] A MoS2 / Mo2CT x The method for preparing the composite material comprises the following steps:
[0063] (1) Take 15 mL of deionized water and place it in the inner lining of a 50 mL reactor. Then add 15 mL of concentrated hydrochloric acid (concentration is 12 mol / L) and 0.5 g of lithium fluoride to the inner lining and stir with a magnetic stirrer until the lithium fluoride is completely dissolved in the deionized water. Then add 0.5 g of MAX phase Mo2Ga2C and continue stirring for 1 hour to obtain a precursor solution for use.
[0064] (2) The liner containing the precursor solution was placed in a reactor, and then the temperature was raised to 160°C and kept at this temperature for 72 hours. After natural cooling, the obtained reaction solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid product was placed in a dryer and dried at 60°C for 12 hours to obtain a gray powder precursor (i.e., Mo2CT x ),spare.
[0065] (3) Take 0.1 g of the precursor prepared in step (2) and dissolve it in 125 mL of water and stir to form a uniformly dispersed MXene aqueous solution. Take 650 mg of sulfur powder and dissolve it in 10 mL of ethylenediamine. After it is completely dissolved, add it dropwise to the MXene aqueous solution. After stirring for 1.5 hours, add dilute hydrochloric acid (concentration of 3 mol / L) until the pH is 1. Continue stirring for 12 hours to obtain a precursor solution for use.
[0066] (4) The precursor solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid was placed in a dryer and dried at 65°C for 15 hours to obtain a yellow-brown powder precursor (i.e., S / Mo2CT x ),spare.
[0067] (5) Take 0.1g of the precursor and place it in a porcelain boat (recorded as porcelain boat 1), then take 1g of sulfur powder and place it in this photo (recorded as porcelain boat 2), place porcelain boat 2 in the upstream of the protective gas flow of the tubular furnace, and place porcelain boat 1 in the downstream of the protective gas flow of the tubular furnace. The protective gas is flowing nitrogen (flow rate is 60 SCCM). After completion, heat to 600℃ at a rate of 3℃ / min and keep warm for 4 hours. After the insulation is completed, cool naturally to obtain the target product MoS2 / Mo2CT x .
[0068] Fifth embodiment
[0069] A MoS2 / Mo2CT x The method for preparing the composite material comprises the following steps:
[0070] (1) Take 15 mL of deionized water and place it in the inner lining of a 50 mL reactor. Then add 15 mL of concentrated hydrochloric acid (concentration is 12 mol / L) and 0.5 g of lithium fluoride to the inner lining and stir with a magnetic stirrer until the lithium fluoride is completely dissolved in the deionized water. Then add 0.5 g of MAX phase Mo2Ga2C and continue stirring for 1 hour to obtain a precursor solution for use.
[0071] (2) The liner containing the precursor solution was placed in a reactor, and then the temperature was raised to 160°C and kept at this temperature for 72 hours. After natural cooling, the obtained reaction solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid product was placed in a dryer and dried at 60°C for 12 hours to obtain a gray powder precursor (i.e., Mo2CT x ),spare.
[0072] (3) Take 0.1 g of the precursor prepared in step (2) and dissolve it in 200 mL of water and stir to form a uniformly dispersed MXene aqueous solution. Take 300 mg of sulfur powder and dissolve it in 10 mL of ethylenediamine. After it is completely dissolved, add it dropwise to the MXene aqueous solution. After stirring for 1.5 hours, add dilute hydrochloric acid (concentration of 3 mol / L) until the pH is 2. Continue stirring for 12 hours to obtain a precursor solution for use.
[0073] (4) The precursor solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid was placed in a dryer and dried at 50°C for 24 hours to obtain a yellow-brown powder precursor (i.e., S / Mo2CT x ),spare.
[0074] (5) Take 0.1g of the precursor and place it in a porcelain boat (recorded as porcelain boat 1), then take 4.5g of sulfur powder and place it in this photo (recorded as porcelain boat 2), place porcelain boat 2 in the upstream of the protective gas flow of the tubular furnace, and place porcelain boat 1 in the downstream of the protective gas flow in the tubular furnace. The protective gas is flowing argon (flow rate is 80 SCCM). After completion, heat to 500℃ at a rate of 2℃ / min and keep warm for 4 hours. After the insulation is completed, cool naturally to obtain the target product MoS2 / Mo2CT x .
[0075] Sixth embodiment
[0076] A MoS2 / Mo2CT x The method for preparing the composite material comprises the following steps:
[0077] (1) Take 15 mL of deionized water and place it in the inner lining of a 50 mL reactor. Then add 15 mL of concentrated hydrochloric acid (concentration is 12 mol / L) and 0.5 g of lithium fluoride to the inner lining and stir with a magnetic stirrer until the lithium fluoride is completely dissolved in the deionized water. Then add 0.5 g of MAX phase Mo2Ga2C and continue stirring for 1 hour to obtain a precursor solution for use.
[0078] (2) The liner containing the precursor solution was placed in a reactor, and then the temperature was raised to 160°C and kept at this temperature for 72 hours. After natural cooling, the obtained reaction solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid product was placed in a dryer and dried at 60°C for 12 hours to obtain a gray powder precursor (i.e., Mo2CT x ),spare.
[0079] (3) Take 0.1 g of the precursor prepared in step (2) and dissolve it in 200 mL of water and stir to form a uniformly dispersed MXene aqueous solution. Take 700 mg of sulfur powder and dissolve it in 10 mL of ethylenediamine. After it is completely dissolved, add it dropwise to the MXene aqueous solution. After stirring for 1.5 hours, add dilute hydrochloric acid (concentration of 3 mol / L) to pH = 3. Continue stirring for 12 hours to obtain a precursor solution for use.
[0080] (4) The precursor solution was centrifuged and washed with deionized water until the pH value was 7. The obtained solid was placed in a dryer and dried at 60°C for 12 hours to obtain a yellow-brown powder precursor (i.e., S / Mo2CT x ),spare.
[0081] (5) Take 0.1g of the precursor and place it in a porcelain boat (recorded as porcelain boat 1), then take 4g of sulfur powder and place it in this photo (recorded as porcelain boat 2), place porcelain boat 2 in the upstream of the protective gas flow of the tubular furnace, and place porcelain boat 1 in the downstream of the protective gas flow in the tubular furnace. The protective gas is flowing nitrogen (flow rate is 40 SCCM). After completion, heat to 800℃ at a rate of 5℃ / min and keep warm for 2 hours. After the insulation is completed, cool naturally to obtain the target product MoS2.
[0082] Performance Testing
[0083] Figure 1 The multilayer Mo2CT prepared in step (2) of the first embodiment x The SEM image of the material shows that the material has no layered structure.
[0084] Figure 2 The multilayer Mo2CT prepared in step (2) of the first embodiment x The XRD image of the material proves that the first embodiment successfully synthesized Mo2CT xMXene products.
[0085] Figure 3 This is a SEM image of the target product prepared in step (5) of the first embodiment. It can be seen from the figure that the target product has both incompletely converted Mo2CT x The structure also has a two-dimensional sheet structure of MoS2 that has been generated.
[0086] Figure 4 TEM images (a and b) of the target product prepared in step (5) of the first embodiment, wherein b is an enlarged view of the box portion of a. It can be seen that the newly generated sheet structure is MoS2 material.
[0087] Figure 5 This is the XRD image of the target product prepared in step (5) of the first embodiment, proving that the first embodiment successfully synthesized MoS2 / Mo2CT x .
[0088] Figure 6 The target product prepared in step (5) of the first embodiment is 0.1A g -1 Discharge curve and Coulomb efficiency under current (electrolyte: ; voltage range: 0.01~3V; surface loading: 1.2 mg cm -2 ). It can be seen that the target product MoS2 / Mo2CT x The discharge capacity of the composite material as a negative electrode material for sodium-ion batteries reached 559 mAh g in the first cycle. -1 , and after 100 cycles, it can still reach 271.2 mAh g -1 , showing excellent electrochemical performance.
[0089] Figure 7 The target product prepared in step (5) of the first embodiment is 1 A g -1 Capacity retention rate under current density. It can be seen that the target product MoS2 / Mo2CT x The composite material can be used as the negative electrode material of sodium ion capacitors, and its capacity retention rate can still reach 58.6% after 5000 cycles.
[0090] Figure 8 The target product (MoS2) prepared in step (5) of the sixth embodiment is 0.1 A g -1 Discharge curves and Coulomb efficiency under current density (electrolyte: ; voltage range: 0.01-4 V; surface loading: 1.12 mg cm -2 ). It can be seen that when MoS2 with a two-position flake structure is used alone as the negative electrode material of the sodium ion capacitor, the first cycle discharge capacity is 880.6 mAhg -1After 100 cycles, the capacity is only 80.9 mAh g -1 .
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A nano-hybrid MoS2 / Mo2CT x A method for synthesizing a composite material, characterized in that: The steps include: (1) Mix the solution containing sulfur powder with Mo2CT x The aqueous solution is mixed, the solvent of the solution containing sulfur powder is ethylenediamine, the pH of the reaction system is adjusted to 1-3, the solid product in the reaction system is separated, washed and dried, and S / Mo2CT is obtained. x ; (2) In an oxygen-isolating environment created by a flowing protective gas, sulfur powder is placed upstream of the protective gas, and the S / Mo2CT x Placed downstream of the protective gas, the sulfur powder is heated to form sulfur vapor, which converts the S / Mo2CT x The Mo2C in the solution is in situ reduced to Mo2S, thus obtaining MoS2 / Mo2CT. x The composite material has a heating temperature of 400-800° C. and a reaction time of 2-4 hours.
2. Nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: In step (1), the Mo2CT x The mass ratio of sulfur to powder is 1:3~8.
3. The nano-hybrid MoS2 / Mo2CT according to claim 2 x A method for synthesizing a composite material, characterized in that: In step (1), the mass concentration of sulfur powder in the solution containing sulfur powder is controlled to be 20-70 mg / mL.
4. The nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: In step (1), the Mo2CT x The aqueous solution is made of Mo2CT x Dispersed in water.
5. The nano-hybrid MoS2 / Mo2CT according to claim 4 x A method for synthesizing a composite material, characterized in that: In step (1), the Mo2CT x Mo2CT in aqueous solution x The concentration was controlled at 0.4~0.8 mg / mL.
6. The nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: In step (1), the solution containing sulfur powder is mixed with Mo2CT x After the aqueous solutions are mixed, the stirring time is not less than 1 hour and then the pH of the reaction system is adjusted to acidic.
7. The nano-hybrid MoS2 / Mo2CT according to claim 6 x A method for synthesizing a composite material, characterized in that: The pH of the reaction system was adjusted using hydrochloric acid, sulfuric acid, nitric acid and acetic acid.
8. The nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: In step (1), after the pH of the reaction system is adjusted, the reaction system is stirred for not less than 12 hours.
9. The nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: In step (1), the solid product is washed to neutrality.
10. The nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: In step (1), the drying temperature is 50-80° C. and the drying time is 10-24 hours.
11. The nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: In step (2), the Mo2CT x The mass ratio to sulfur powder is 1:10~50.
12. The nano-hybrid MoS2 / Mo2CT according to claim 11 x A method for synthesizing a composite material, characterized in that: The heating rate is 2-5°C / min.
13. The nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: In step (2), the protective gas includes any one of argon, nitrogen or helium, or a combination of at least two of them.
14. The nano-hybrid MoS2 / Mo2CT according to claim 1 x A method for synthesizing a composite material, characterized in that: The flow rate of the protective gas is 40-100 SCCM.
15. Nano-hybrid MoS2 / Mo2CT obtained by the synthesis method according to any one of claims 1 to 14 x A composite material, characterized in that The two-dimensional structure of MoS2 is in situ bonded to the Mo2CT x The conductive substrate surface and the conductive substrate.
16. MoS2 / Mo2CT according to claim 15 x Composite material or nano-hybrid MoS2 / Mo2CT obtained by the synthesis method according to any one of claims 1 to 14 x Application of composite materials in energy storage devices.
17. The use according to claim 16, characterized in that MoS2 / Mo2CT according to claim 15 x Composite material or nano-hybrid MoS2 / Mo2CT obtained by the synthesis method according to any one of claims 1 to 14 x The composite material is used as the negative electrode material of sodium ion batteries and sodium ion capacitors.
Citation Information
Patent Citations
Mo2C@MoS2 heterojunction and preparation method and application thereof
CN113178556A
High capacity electrodes enabled by 2d materials in a viscous aqueous ink
EP3680962A1